Parcours et interlexis (la relation de concession) - Catherine Filippi-Deswelle (Corela)
I wish to discuss the concept of scanning in connection with concessive utterances with “though”, “although” and “even though” in which scanning appears as a specific form of an operation of iteration on a domain that should be carefully identified – an operation finding its resolution in the assertion of a predicative relationship that contradicts what could be expected in the situation of utterance. The concessive operation makes it possible to re-introduce a qualitative unstability where there is initially a preconstructed (abstract, ideational) wholeness, in such a way as there is always a remaining trace. In addition to the disclosure of this operation of qualitative otherness (Filippi-Deswelle 2003), which is a factor concessive markers have in common, it will be interesting to study the scanning operation that is specifically associated with the markers “all” and “even” linked with “though” in the concessive interpretation (totalizing scanning for “all” and homogenizing scanning for “even”) in order to clarify their roles in the building up of a restricted concessive paradigm. I will endevaour to show briefly how “the iterative turns into the intensive” (Bourquin, 1984).